Penggunaan Media Bergambar Pada Efektivitas Belajar Gerakan Sholat Anak Usia Dini Di Ra As-Syarief Desa Sibanggor Jae: The Use of Picture Media on the Effectiveness of Learning Early Childhood Prayer Movements at Ra As-Syarief Sibanggor Jae Village - Fhatri, Zonalisa; Rangkuti, Nur Azizah (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2024)
The Use of Picture Media on the Learning Effectiveness of Early Childhood Prayer Movements at RA As-Syarief, Sibanggor Jae Village, Early Childhood Islamic Education Study Program (PIAUD), The Islamic Education Departmen of Tarbiyah and Teacher Training Faculty at the Mandailing Natal State of Islamic College, Supervisor I : Ali Masran Daulay S.Pd.,M.A, Supervisor II: Syamsiah Depalina Siregar, M.Pd. The purpose of this study was to obtain accurate information about how the use of illustrated media has on the effectiveness of learning early childhood prayer movements at RA As-Syarief Sibanggor Jae Village, what is the effect of illustrated media on the effectiveness of learning early childhood prayer movements at RA As-Syarief Village Sibanggor Jae. This research is a study to describe the Use of Picture Media on the Learning Effectiveness of todler Prayer Movements at RA As-Syarief, Sibanggor Jae Village. The research method used in this research is descriptive research with a qualitative approach, namely describing the results of data processing with words and general descriptions that occur in the field. The process of collecting data researchers used the method of observation, interviews, and documentation. The results of this study revealed the findings that through the media with pictures of the prayer movements, it was easier for students to absorb learning material and easier to remember than when the teacher only told stories in front of them. This pictorial media has an effect on lower grade children, they are more enthusiastic about learning when learning materials are packaged in such a way and combined with the right media. There is also the influence of the development of the practice of children's prayer movements. The use of visual learning media has a positive impact on increasing the development of children's prayer movement practices. In the prayer movement indicator, most of the children were able to carry it out according to the movements that were appropriate for children aged 5-6 years at RA As-Syarief, Sibanggor Jae Village.